1988
DOI: 10.1037/h0089748
|View full text |Cite
|
Sign up to set email alerts
|

Huntington's disease: Therapy strategies.

Abstract: Case reports are offered to illustrate a modified psychoeducational approach to single-family therapy and multiple-family therapy with families with Huntington's disease. Single-family therapy was especially helpful in solving problems related to specific family developmental crises and to shifts in family roles and hierarchies resulting from the progressive worsening of Huntington's symptoms. The mobilization of hope and altruism and a lessening of the sense of isolation and helplessness in coping with the il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
1
16
0
1
Order By: Relevance
“…These families, for generations had experienced the kind of ambiguous loss described by Boss in which affected relatives, in the terminal phases of HD, were physically present but psychologically absent. Their family history and its cumulative affects on family dynamics that often resulted in conflict, alcoholism, physical abuse, and suicide (Murburg et al, 1988) poorly prepared them to cope with the information revealed by the test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These families, for generations had experienced the kind of ambiguous loss described by Boss in which affected relatives, in the terminal phases of HD, were physically present but psychologically absent. Their family history and its cumulative affects on family dynamics that often resulted in conflict, alcoholism, physical abuse, and suicide (Murburg et al, 1988) poorly prepared them to cope with the information revealed by the test.…”
Section: Discussionmentioning
confidence: 99%
“…Understandably, families with a long history of loss because of inherited diseases that were misdiagnosed or unexplained, as was the case for HD, are predisposed to particular difficulty (Byng‐Hall, 1991; Murburg, Price, & Jalali, 1988; Rolland, 1999). Whatever their prior explanations for the death of relatives, their fates are now intertwined.…”
mentioning
confidence: 99%
“…In this way the multiple family paradigm has inspired more traditional therapeutic activities in general mental health services, such as relative support and carer groups, and it is now a well-established ingredient in the work with people with schizophrenia (Kuipers et al, 1992). Multiple family therapy is now also practised in many other presentations and conditions (O'Shea and Phelps, 1985), including drug and alcohol abuse (Kaufman and Kaufman, 1979), chronic medical illness (Gonsalez et al, 1989;Steinglass, 1998), Huntingdon's disease (Murburg et al, 1988), child abuse (Asen et al, 1989), eating-disorder patients (Dare and Eisler, 2000;Scholz and Asen, 2001;Slagerman and Yager, 1989), and more specifically bulimia nervosa (Wooley and Lewis, 1987), and a mixture of in-and outpatient children and adolescents presenting with a variety of problems (Wattie, 1994). It is likely that its cost-effectiveness in times of dwindling resources does explain in part the increasing popularity of the multiple family therapy approach.…”
Section: Reflections and Further Perspectivesmentioning
confidence: 99%
“…The distress patients experience when being diagnosed with HD is believed to be partly related to their previous experiences of others with the disease, including the effects that HD has had on their lives of their own parents or other close relatives (Tyler, 1991). If they have children, the guilt they experience for possibly having transmitted the gene to them, further contributes to their distress (Hayden et al, 1980;Murburg, Price, & Jalali, 1988). If they have children, the guilt they experience for possibly having transmitted the gene to them, further contributes to their distress (Hayden et al, 1980;Murburg, Price, & Jalali, 1988).…”
mentioning
confidence: 99%